3-D modeling and simulation of fluidic microsystems for biological fluids analysis - Minas, Graça (2005)
This paper describes a three-dimensional fluid dynamic model that is suitable for accurate simulation of on-chip liquid handling and mixing. The fluidic die (or mixer) is an integrated part of a biological microsystem for biological fluids analysis. It is designed for enabling a mixing process based on diffusion, which allows an easy-to-fabricate and low-cost mixer. The fabrication is based on planar technology using IC-compatible lithography. Computer simulations have been carried out to analyze the details of the flow and the diffusion in the mixer in order to derive the appropriate design criteria for the layout. The mixer has been fabricated using glass micro-machining with SU-8 techniques and wafer-to-glass bonding. Its performance is successfully demonstrated for serum albumin concentration detection.